Mitigation of 3-monochloropropane 1,2 diol ester and glycidyl ester in refined oil – A review - Yung, Yen Li; Shyam Lakshmanan; Sivakumar Kumaresan; Chu, Chi Ming; Tham, Heng Jin (Elsevier Ltd., 2023)
The 3-Monochloropropane-1, 2-diol ester (3-MCPDE) and glycidyl ester (GE) are formed at high processing temperatures with the presence of respective precursors. Both are potentially harmful to humans, causing adverse health impacts including kidney damage, reproductive problems, and increased risk of cancer. The presence of 3-MCPDE and GE in palm oil is of particular concern because of its widespread use by the food industry. There are a variety of methods for reducing 3-MCPDE and GE. For example, water washing eliminates mostly inorganic chlorides that, in turn, reduce the formation of 3-MCPDE. 3-MCPDE has also been reduced by up to 99% using combinations of methods and replacing stripping steam with alcohol-based media. Activated carbon, clay, antioxidants, potassium-based salts, and other post-refining steps have positively lowered GE, ranging from 10 to 99%. Several approaches have been successful in reducing these process contaminants without affecting other quality metrics.